SPACE DIPLOMACY AND SOCIAL DYNAMICS: CHARTING INDIA’S TRAJECTORY IN GLOBAL COLLABORATIONS - Parveen, Huma; Verma, Rajesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Space diplomacy involves utilizing space science and technology to achieve foreign policy goals and enhance national space capabilities. The objectives of space programs in the Global South include applications in agriculture, water resource management, weather forecasting, telecommunications, telemedicine, and education. With over seventy countries having space agencies, particularly in the Global South, cooperation in space endeavors relies on diplomacy, international treaties, and agreements to ensure peaceful uses of space technology. While many countries control satellites, only a few possess launch capabilities, with regional and multilateral bodies playing key roles in technology development and regulatory frameworks. Countries in the Global South are striving to enhance their space capabilities through agencies, bilateral agreements, and participation in regional space bodies like the African Space Agency and the Latin American and Caribbean Space Agency. Through this paper, an attempt is made to analyse India’s space diplomacy and social dynamics and its trajectory in global collaborations. The research focuses on Major space diplomacy initiatives in the Global South; Space diplomacy challenges in the Global South; and the politics of India’s space programme and its growth trajectory